2015
DOI: 10.1021/cs5020157
|View full text |Cite
|
Sign up to set email alerts
|

Rh/ZrP2O7 as an Efficient Automotive Catalyst for NOx Reduction under Slightly Lean Conditions

Abstract: The three-way catalyst performances of honeycomb-coated Rh catalysts were studied on several metal phosphate supports (AlPO4, YPO4, ZrP2O7, and LaPO4) using various simulated exhausts with different air-to-fuel ratios (A/F). These supports significantly improved the NO x purification (deNO x ) efficiency under slightly lean conditions (14.6 < A/F ≤ 15.3) as compared with conventional Rh/ZrO2 catalysts. The deNO x activity exhibited the following sequence of increasing the mean electronegativity of the suppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
48
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 52 publications
(67 citation statements)
references
References 47 publications
(69 reference statements)
11
48
2
Order By: Relevance
“…In both cases, Rh/ZrP 2 O 7 showed a higher NO x conversion activity compared with Rh/ZrO 2 . These results of powdered catalysts are consistent with those of cordierite honeycomb coated catalysts in our previous study [15]. This suggests that the higher deNO x performance is the intrinsic property of the Rh/ZrP 2 O 7 catalyst.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…In both cases, Rh/ZrP 2 O 7 showed a higher NO x conversion activity compared with Rh/ZrO 2 . These results of powdered catalysts are consistent with those of cordierite honeycomb coated catalysts in our previous study [15]. This suggests that the higher deNO x performance is the intrinsic property of the Rh/ZrP 2 O 7 catalyst.…”
Section: Resultssupporting
confidence: 91%
“…More interestingly, this unusual redox behavior of the Rh catalysts causes a positive impact on their lean NO x purification (deNO x ) performance. One typical example can be seen for the Rh catalyst supported on ZrP 2 O 7 , which exhibited the highest NO x conversion under slightly lean condition (A/F ≤ 15.0) among various phosphate materials in our previous study [15].…”
Section: Introductionmentioning
confidence: 68%
See 2 more Smart Citations
“…For example, Tanabe et al [4] reported that Rh interacts strongly with Nd 2 O 3 , resulting in Rh sintering suppression by the formation of Rh-O-Nd bond. Machida et al [5][6][7] developed metal phosphate materials such as tridymiteAlPO 4 and ZrP 2 O 7 as a robust support material producing optimum interactions with Rh species, owing to the high thermal stability and the high dispersion of Rh species anchored onto the surface. Kawabata et al [8,9] reported that Rh catalyst supported on La-containing ZrO 2 showed high performance for the removal of NOx and hydrocarbons.…”
Section: Introductionmentioning
confidence: 99%